O Impacto Clínico e Económico do Suporte Nutricional no Doente Desnutrido - Ana Sofia Valongo (Formifarma, LDA., 2013)
Introduction: Nutritional status determines the patient's clinical progression, being unquestionable that adequate nutritional support is an advantage when considering the treatment's global approach. Objectives: This review intends to approach how undernutrition and adequate parenteral and enteral nutritional support (using an enteral feeding tube) affect clinical and economic outcome in a hospital setting. Methods: Literature review included clinical trials, meta-analysis, original papers, review articles and guidelines available from databases such as PubMed Central and Google Scholar. Results: Undernutrition in the hospital setting has high prevalence, is not always identified by healthcare professionals and is related to diminishment of muscular, respiratory and immune functions, having a negative action upon the treatment and scarring of wounds. It increases surgical complications, risk of infection, duration of assisted ventilation and hospitalization time and costs. Screening and nutritional assessment, as well as early treatment of undernourished people is cost-effective. Nutritional support aims at providing enough energy intake to cover the patient's needs in order to prevent the onset of undernutrition or correct pre-existing undernutrition. In the hospital setting, nutritional approach includes, among others, enteral nutrition (EN) and parenteral nutrition (PN). The impact of these in the patient's nutritional status is crucial on the decrease of morbidity and mortality and, consequently, on the reduction of hospitalization costs. EN is the first-line approach when oral intake is not possible or is unsuitable, allowing for the reduction of infectious complications and economic costs, when compared to PN. Conclusions: Nutritional assessment upon hospital admittance is essential and must not be disregarded by healthcare professionals and healthcare systems, as it allows to correct existing undernutrition and prevents nutritional status decline during hospitalization, enabling improved clinical outcome and cost reduction.